Estresse e coping entre técnicos e auxiliares de enfermagem de um hospital universitário - Stekel, Lilian Medianeira Coelho (2011)
With the advancement of technology and innovations in medical institutions, many studies are focusing on the people who work in this environment, since such changes can provoke insecurity and compromise the physical and emotional balance of the professionals involved. In this sense, this study aims to identify the general occupational stress of the nurses assistants and technicians, as well as verify the strategies of confrontation used by these professionals in the hospital environment. It is a transversal study, with a quantitative approach, conducted at the College Hospital of Santa Maria (HUSM), Rio Grande do Sul. The data were collected from a self-applied questionnaire. In order to identify the stress of these workers, the Work Stress Scale (WSS) was used, elaborated and validated by Paschoal and Tamayo (2004), composed of 23 items, which form only one factor. To evaluate the strategies of coping, the Folkman e Lazarus's Ways of Coping Questionnaire (1984) was applied, which is composed of 66 items, and was translated and validated by Savóia, Santana and Mejias (1996). The eight factors proposed by Lazarus e Folkman (1984) were considered in the analysis of the data. The data were stored and organized in an electronic worksheet, in the Excel program (Office XP) and, later, analyzed with the support of the software Statistical Analysis System (version 8.02) and Statistica (version 7.01). The results were considered statistically significant at p<0.05, with a 95% confidence interval. The subjects were 218 nurse technicians and 163 nurses assistants, totaling 381 workers, the majority were women (87.1%), and the average age was 43.04 years old (± 8.77). They had 12.87 years of service time at HUSM (±9.1) and 8.7 years (±7.42) of service in the current unit. It was noted that 74.5% of these professionals did not have a college degree and 85.6% did not have another job. It also can be observed that the majority of these nursing professionals had attended technical school (72.4%). In relation to stress, 59.84% of these professionals obtained averages between 2.01 and 3.00, verified as a medium level of stress. The workers working in the units with higher averages of stress, were in adult ICU (2.85), Pediatric Clinic (2.39) and the post-anesthesia care unit (2.46). The nurse technicians and assistants with smaller averages of stress were the ones working in the medical clinic II (1.92) and cardiac ICU (1.99). Regarding coping factors, the resolution to the problems was the strategy most used by these workers. In this study, it could be verified that there is not a significant difference between stress and coping in the occupations evaluated. However, a significant negative correlation between service time at HUSM and the social support factor was identified, as well as in the service time in the same unit with the social support factor and the resolution of problems. Low positive correlations between the coping factors and stress were also verified. In conclusion, the nurse technicians and assistants had a medium level of stress, which empirically, can be directly related to the use of confrontation strategies aimed at a solution for the problems.